JOHN GARSTANG AND SAKCAGOZU EXCAVATIONS (1908-1911) - ÇİFÇİ, ALİ (EGE UNIV, 2019)
Sakcagozu, located in the Nurdagi district of Gaziantep province, was excavated by John Garstang between 1908 and 1911 during two excavation seasons. Of the 11 identified layers, IX. and X contain the Neo-Hittite palace enclosure, which was surrounded by walls and had a 'bit hilani' structure decorated with reliefs. The excavation records, photographs and materials held at the University of Liverpool's Garstang Museum of Archaeology, as well as materials held at the Archaeological Museum of Istanbul were utilised for this study. Garstang's relations with the director of the Imperial Museum Osman Hamdi Bey, and Sir Edwin Pears from the British Consulate in Istanbul at the time, will also be considered. I will also consider how Garstang obtained the excavation permit for the Sakcagozu and his subsequent interest in the Neo-Hittite reliefs found here.
Keywords: John Garstang; Sakcagozu; Coba Hoyuk; Neo-Hittite; reliefs